PEMANFAATAN WEBSITE WORDWALL DALAM MATA KULIAH SENI MUSIK MATERI CHORD GITAR UNTUK MENGIDENTIFIKASI HASIL BELAJAR MAHASISWA PGMI UIN WALISONGO - Faiq Ridlo Al Amin; Arsan Shanie (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2023)
The development of technology has brought a significant impact in education, allowing the use of more interactive and effective media in the learning process, including video, audio, and images. Technology also supports distance learning, providing flexibility for students to learn from anywhere and at any time, overcoming accessibility and mobility issues in education. This study used descriptive qualitative method with a focus on students of PGMI 3A class at UIN Walisongo. Data collection involved observation, interviews, and documentation to get a picture of learning activities.Wordwall, as a web-based digital platform, is explained as a tool to create interactive learning. The platform provides quiz-based educational game templates to measure learners' understanding. In the context of music learning, Wordwall can increase interest in learning and provide variety in student evaluation. This research underscores the importance of technology integration, particularly Wordwall, in learning to create a more engaging and interactive learning experience.